Assessment report on hydrological implications of “Satha Dhan” cultivation in the Central Plain Zone of Uttar Pradesh, India - Deb, Proloy; Banerjee, Deep; Urfels, Anton; Singh, Sudhanshu (International Rice Research Institute, 2025)
India is an agrarian nation, leading the total irrigated agricultural area across the world. Intensive irrigation application has caused serious pressure on groundwater resources in the region, especially in the areas where summer rice is widely grown. This study synthesizes summer rice cultivation in the northern and central Uttar Pradesh (UP), India, where most irrigation depends on groundwater. Specific information on this cropping pattern and implication on natural resources is hardly documented in scientific literature. Using satellite images and computer-based modeling techniques, the study mapped summer rice acreage and potential irrigation application (in terms of depth and volume) in seven districts of UP in 2023. Furthermore, this report also quantified the uncertainties associated with these simulations. The results show that both land area for summer rice and water needed to grow vary significantly across the districts. In most districts, summer rice uses less than 30% of yearly available groundwater. However, in districts with large rice area, summer rice uses more than 70% of the annual extractable groundwater aggregating to 2568 million m3. Satellite records for the last decade show groundwater levels are steadily declining, especially in some of the key districts, highlighting the urgent need for multidimensional evidence generation at local scale, agronomic standards emphasizing sustainable water management, and growing less water-demanding crops.